Synthesis and characterization of star‐shaped PLLA with sorbitol as core and its microspheres application in controlled drug release. Issue 27 (4th April 2015) - Teng, Lijing; Nie, Wangyan; Zhou, Yifeng; Song, Linyong; Chen, Pengpeng
ABSTRACT The purpose of this study was to investigate the suitability of a six‐arm star‐shaped poly(l‐lactide)s (s‐PLLA) as controlled drug carriers for hydrophobic drug molecules. First, s‐PLLA was synthesized by ring‐opening polymerization of l‐lactide using sorbitol as initiator and stannous octoate as catalyst. The structure and molecular weight (Mw) of s‐PLLA was characterized with 1H NMR, 13C NMR, and GPC. Second, rifampicin (RIF) used as a model drug was encapsulated within the microspheres of s‐PLLA via oil‐in‐water emulsion/solvent evaporation technique. The morphology, drug encapsulation efficiency (EE), and in vitro release behavior of the prepared microspheres were studied in details. Results indicated that the average diameters of s‐PLLA microspheres can be controlled between 8 and 20 µm by varying the copolymer's concentration or Mw. The EE of RIF was mainly determined by the concentration of s‐PLLA. The in vitro study showed that the burst release behavior can be depressed by increasing the Mw of the s‐PLLA. Present work suggests that the synthesized s‐PLLA could be used as a new material for drug delivery. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42213.